Anodic titania nanotubes decorated with gold nanoparticles produced by laser-induced dewetting of thin metallic films - Katarzyna Grochowska (Nature Portfolio, 2020)
Abstract Herein, we combine titania layers with gold species in a laser-supported process and report a substantial change of properties of the resulting heterostructures depending on the major processing parameters. Electrodes were fabricated via an anodisation process complemented with calcination to ensure a crystalline phase, and followed by magnetron sputtering of metallic films. The obtained TiO2 nanotubes with deposited thin (5, 10 nm) Au films were treated with a UV laser (355 nm) to form Au nanoparticles on top of the nanotubes. It was proven that selected laser working parameters ensure not only the formation of Au nanoparticles, but also simultaneously provide preservation of the initial tubular architecture, while above-threshold laser fluences result in partial destruction (melting) of the top layer of the nanotubes. For almost all of the samples, the crystalline phase of the nanotubes observed in Raman spectra was maintained independently of the laser processing parameters. Enhanced photoresponse up to ca 6 mA/cm2 was demonstrated by photoelectrochemical measurements on samples obtained by laser annealing of the 10 nm Au coating on a titania support. Moreover, a Mott–Schottky analysis indicated the dramatically increased (two orders of magnitude) concentration of donor density in the case of a laser-treated Au–TiO2 heterojunction compared to reference electrodes.